1995
DOI: 10.1021/bi00030a013
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Activity of the Endoplasmic Reticulum Ca2+-ATPase of Bovine Adrenal Cortex

Abstract: It is generally accepted that the ryanodine receptor and the inositol 1,4,5-trisphosphate receptor play major roles in the complex mechanisms by which agonists increase intracellular Ca2+ concentration. In these mechanisms, the endoplasmic reticulum Ca(2+)-ATPase has been attributed an accessory role of refilling the intracellular Ca2+ store. In the present study, the activity of the microsomal Ca(2+)-ATPase of bovine adrenal cortex was investigated. We show that the Ca(2+)-pumping activity of the Ca(2+)-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…InsP 3 Binding Assay of the Immunoprecipitated InsP 3 Receptor. Bovine adrenal cortex membranes were prepared as previously described (26). Membranes (1 mg of protein) were solubilized, and the InsP 3 receptor was immunoprecipitated as described in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…InsP 3 Binding Assay of the Immunoprecipitated InsP 3 Receptor. Bovine adrenal cortex membranes were prepared as previously described (26). Membranes (1 mg of protein) were solubilized, and the InsP 3 receptor was immunoprecipitated as described in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…Ins(1,4,5)P 3 Derivatives Binding Assay. Bovine adrenal cortex microsomes were prepared as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Bovine adrenal cortex microsomes were prepared as previously described. 46 Bovine adrenal microsomes were incubated for 30 min at 0 °C in a medium containing 25 mM Tris/HCl buffered at pH 8.5, 100 mM KCl, 20 mM NaCl, 5 mM KH2PO4, and 1 mM EDTA in a final volume of 500 µL with the appropriate concentration of [ 3 H]Ins(1,4,5)P3 (0.9 nM), Ins(1,4,5)P3, and Ins(1,4,5)P3 derivatives. Nonspecific binding was determined in the presence of 1 µM Ins(1,4,5)P3.…”
Section: (()-145-tri-o-allyl-23-di-o-benzyl-epi-inositol (24)mentioning
confidence: 99%
“…All hitherto identified TRP type channels, the best characterized and the most likely channel type involved in receptormediated Ca signaling, are not IP 3 -, ryanodine-, cADPribose-, or NAADP-sensitive. Instead, constitutionally open ion channels have been found in Ca-storing microsomal vesicles using the 45-Ca uptake technique showing rapid equilibration with external Ca, ATP, and IP 3 and other large anions via open cation and anion channels (Clairmont et al, 1992;Lange and Brandt, 1993b;Poitras et al, 1995;. Several studies have shown that Ca-storing vesicles of different origin exhibit a constitutionally open influx pathway for Ca, which clearly contradicts the hypothesis of an active ATP-dependent Ca pumping mechanism located in the vesicle membrane (Schmid et al, 1990;Lange and Brandt, 1993b).…”
Section: Points Of Criticism In the Current Conceptmentioning
confidence: 99%